131k views
4 votes
Which is the simplified form of the expression

Which is the simplified form of the expression-example-1
Which is the simplified form of the expression-example-1
Which is the simplified form of the expression-example-2
Which is the simplified form of the expression-example-3
Which is the simplified form of the expression-example-4
Which is the simplified form of the expression-example-5
User Bland
by
5.9k points

1 Answer

6 votes

Answer:


\displaystyle A=( 4 )/( x^(14) y^(8))

Explanation:

Properties of Powers

The algebraic expression called power has the form x^y where x is called the base and y is called the exponent.

Powers have some properties, some of which we'll recall below


(x^a)^b=x^(ab)


(x^a)(x^b)=x^(a+b)


\displaystyle (x^a)/(x^b)=x^(a-b)


\displaystyle x^(-a)=(1)/(x^a)


\displaystyle x^(a)=(1)/(x^(-a))

We'll use those properties to simplify the expression


\displaystyle A=\left( ( (2)^(-3)(x^(-3)) (y^2) )/((4^(-2)) (x^4) (y^6)) \right)^2

Taking the power 2 of every term


\displaystyle A=( (2)^(-6)(x^(-6)) (y^4) )/((4^(-4)) (x^8) (y^(12)))

Moving the terms with negative exponent to its opposite side


\displaystyle A=( (2)^(-6) (4^(4))(y^4) )/( (x^8)(x^(6)) (y^(12)))

Operating the explicit same bases


\displaystyle A=( (2)^(-6) (4^(4)) )/( (x^(14)) (y^(12-4)))

Since
4^4=(2^2)^4=2^8


\displaystyle A=( (2)^(-6) (2^8) )/( (x^(14)) (y^(12-4)))

Operating the remaining like bases subtractions


\displaystyle A=( (2^2) )/( (x^(14)) (y^(8)))

Finally


\displaystyle A=( 4 )/( x^(14) y^(8))

User Mitchkman
by
5.6k points